Implementasi WordPress Berbasis Virtual Machine pada Sistem Operasi Linux - Princess An-Najwa Amin; Aida Nurul Fitri; Fauzi Abdul Rohim; Muhammad Fikri (Journal of Engineering and Applied Technology, 2025)
The development of information technology has increased the demand for content management systems that are easy to use and flexible for website management. WordPress is widely used as a platform for building informational websites. This study aims to implement WordPress on a Linux operating system based on a Virtual Machine as a medium for website development and testing. The research methods include system design, virtual network configuration, installation of the web server and database server, and system functionality testing. The implementation is carried out using a Linux server environment with Apache as the web server and MySQL as the database server. The results show that WordPress can be successfully installed and run in a virtual environment and accessed through a local network using an IP address and a local domain. This implementation demonstrates that Virtual Machine technology is an effective and efficient solution for WordPress-based website development without requiring a physical server.